Establishment of an arabinose-inducible system in Stenotrophomonas maltophilia - Huang, Yi-Wei; Hu, Rouh-Mei; Chiang, Yu-Ting; Chung, Tsao-Chuen; Chung, Tung-Ching; Yang, Tsuey-Ching (Folia microbiologica, 2011)
A pBBad22T-derived conditioned arabinose (Ara)-inducible expression system was evaluated in Stenotrophomonas maltophilia (an opportunistic pathogen and has gained increasing attention as a cause of healthcare-associated infection). S. maltophilia cannot grow well when Ara is the sole available carbon source. The induction kinetic study, optimal inducer concentration determination, and depletion experiment were performed by using a xylE gene fusion construct, pBxylE, to monitor the expression of pBBad22T in S. maltophilia. For induction survey, the expression of catechol 2,3-dioxygenase (C23O), encoded by xylE gene, continuously increases during an 8-h induced course and can be modulated by different inducer concentrations. The applied induction condition of pBBad22T in S. maltophilia is the inducer concentration ranging from 0.1% to 0.5% for an induction time of 4 h. For repression evaluation, the C23O expression is rapidly turned off within 30 min after the removal of Ara. Accordingly, the established Ara-inducible system can provide a convenient tool for the study of S. maltophilia.
Keywords: regulace genové exprese u bakterií; Gene Expression Regulation, Bacterial; Bacterial Proteins; Stenotrophomonas maltophilia; katechol-2,3-dioxygenasa; Catechol 2,3-Dioxygenase; Arabinose; arabinosa; bakteriální proteiny